Effects of Galgeungyulpitang on Cellular Production of Melanin and Elastase - Na Young Jo; Eun Yong Lee; Cham Kyul Lee; Jeong Du Roh (MEDrang Inc., 2019)
Background This study was designed to investigate the potential effects of Galgeungyulpitang for whitening and elasticity treatment by examining its effect on melanoma cells. Methods The effects of Galgeungyulpitang on B16/F10 melanoma cell viability, production of melanin, tyrosinase and elastase, were investigated. Cell viability was measured by colorimetric assay that assesses cell metabolic activity (MTT assay). Melanin was measured by Hosei's method, tyrosinase was measured by Yogi's method and elastase was measured by James's method. Results At concentrations higher than 500 μg/mL Galgeungyulpitang, cell viability was significantly reduced (p ≤ 0.05). At concentrations of 500 μg/mL and lower, morphological changes were not observed. The rate of melanin synthesis was significantly reduced to 73.49% ± 2.92% at a concentration of 500 μg/mL Galgeungyulpitang compared with untreated cells (p < 0.05). Extracellular tyrosinase production was not significantly decreased in vitro, however, intracellular tyrosinase production was significantly reduced to 76.06% ± 2.17% when treated with Galgeungyulpitang at a concentration of 500 μg/mL compared with the control (p < 0.05). Elastase Type 1 production was significantly reduced to 74.98% ± 3.24% and 69.62% ± 4.66% at concentrations of 250 and 500 μg/mL Galgeungyulpitang, respectively (p < 0.05). Elastase Type 4 production was significantly reduced to 72.77% ± 3.52% at concentrations of 250 and 500 μg/mL (p < 0.05). Conclusions The results in this study showed that Galgeungyulpitang may inhibit melanin and tyrosinase synthesis, and inhibit elastase production, suggesting that Galgeungyulpitang may be potentially beneficial for skin whitening and loss of skin elasticity treatments.